Pre-Employment Readiness Among Final Year Student Nurses (Journal of Engineering and Health Sciences, 2017)
This study is to describe the factors that can affect the readiness of the final year student nurses toward the nursing profession. Aim of the study is to identify the readiness for the employment as a Registered Nurse. Besides that, this study also try to determine the the level of the student readiness toward nursing profession and to identify the appropriate action to be implemented by the institution. Results of this study show that the majority of students are ready to hold a registered nurse post. However, the confidence and motivation level is detected to be at low satisfactory level. Preparations in terms of pre-employment also less complete. Conclusion of study indicates that, these students needs assistance in order to raise the level of motivation and confidence. Guidance and assistance is also required in order to explain to them the appropriate way to prepare for the needs of pre-employment process.